1991
DOI: 10.1055/s-0038-1647467
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism and Bleeding Tendency in Congenital Factor XII DeficienCy - A Study on 74 Subjects from 14 Swiss Families

Abstract: SummaryIn order to assess the clinical implications of hereditary F XII deficietrcy, all available members of Swiss families with F XII deficiency were investigated. Based on the F XII: C values and the family pedigree, the 74 subjects, aged 8-–82 years, were classified as homozygotes/double heterozygotes for F XII deficiency (n = 18), as obligatory (n = 20) or possibly (n = 25) heterozygotes, respectively, and as norrnals (n = 11). None of the 18 subjects with F XII: C <0.01 U/ml and only one possibly hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0
10

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 24 publications
5
113
0
10
Order By: Relevance
“…However, in vivo these individuals rather seem to have a higher incidence of thromboembolism (9,10), as was illustrated by the clinical course of the index case, Mr. Hageman, who died of pulmonary embolism (18,19). The data presented here show that activation of the contact system contributes to plasminogen activation, induced in vivo by intravenous administration of DDAVP.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, in vivo these individuals rather seem to have a higher incidence of thromboembolism (9,10), as was illustrated by the clinical course of the index case, Mr. Hageman, who died of pulmonary embolism (18,19). The data presented here show that activation of the contact system contributes to plasminogen activation, induced in vivo by intravenous administration of DDAVP.…”
Section: Discussionmentioning
confidence: 53%
“…[8]) in fibrinolysis is supported by several lines of evidence. First, patients with severe factor XII deficiency have a higher incidence of thromboembolic events, which might be attributed to an impaired fibrinolytic activity (9,10). Second, recent observations in patients with hereditary angioedema, which is caused by a deficiency ofthe major inhibitor of the contact system, Cl-inhibitor, have shown that increased activity of the contact system is associated with an enhanced plasmin generation (11).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors did not find a decrease of FXII to be a determinant of thrombosis (Lämmle et al, 1991;;Koster et al, 1994) or CVD (Kelleher et al,1992;Kohler et al, 1999). The FXII 46 C>T mutation was found to be associated with diminished plasma FXII levels in homozygous and heterozygous carriers in comparison with normal individuals, principally in the homozygous form.…”
Section: Fxii 46c>tmentioning
confidence: 95%
“…We have demonstrated previously that HKa and PAI-1 compete for proximal binding sites within the N-terminal "somatomedin B" domain of VN (24). Experimental evidence from in vitro and in vivo studies renders HK antirather than prothrombotic; a prothrombotic phenotype was reported for kininogen-deficient rats (30), and patients deficient in kininogen or other proteins of the contact phase system are at increased risk for thrombosis (31)(32)(33)(34). In particular, HK/HKa may regulate pericellular plasmin generation by modulating plasma kallikrein-dependent formation of urokinase plasminogen activator (uPA) (35), a reaction dependent on the binding of plasma prekallikrein to HK domain 6 (36).…”
mentioning
confidence: 99%